Interdependent relationship between depression and Internet gaming disorder in parent-child dyads: The mediating role of family relationship and gaming time - Qian Li; Yilun Huang; Samuel Yeung-Shan Wong; Winnie W. S. Mak; Xue Yang (PLoS ONE, 2026)
Background and objective A well-established link exists between depression and Internet gaming disorder (IGD) at the individual level, while it remains unexplored within the family system. This study aims to investigate the interdependent relationship between parent and adolescent depression and IGD, and to identify the potential mechanisms. Methods A cross-sectional dyadic study was conducted with adolescents and their parents (primary caregiver) in Hong Kong. Adolescents completed anonymous surveys in classrooms, and parents completed online surveys via WhatsApp or phone interviews. The Actor-Partner Interdependence Model (APIM) and Actor-Partner Interdependence Mediation Model (APIMeM) were utilized to test the interdependence and mediators between depression and IGD in parent-child dyads, respectively. Results A total of 1,277 parent-child dyads were included. Depressive symptoms in parents (β = 0.072) and adolescents (β = 0.273, both p < 0.05) were positively associated with their own IGD symptoms (actor effect). Adolescent depressive symptoms were positively associated with parental IGD symptoms (β = 0.078, p < 0.05). Family relationships and adolescent gaming time mediated the association of adolescent depressive symptoms with adolescent IGD symptoms (indirect effect accounting for 21.5%) and parental IGD symptoms (74.3%). Conclusions Adolescent depressive symptoms were positively associated with their own and parental IGD symptoms, which were mediated by adolescent-reported family relationships and adolescent gaming time. The influence of adolescents’ mental health problems on parents’ problematic behaviors within the family system should not be overlooked.